2022
DOI: 10.1002/jsfa.11897
|View full text |Cite
|
Sign up to set email alerts
|

Study on gel properties of lysozyme‐free egg white before and after Lactiplantibacillus plantarum fermentation

Abstract: BACKGROUND Isolation of lysozyme from egg white (EW) using ion exchange resin adsorption method generates large quantities of lysozyme‐free egg white (LFEW) with poor gelling property. To maximize the applications of LFEW, the effect of Lactiplantibacillus plantarum fermentation on the gel properties of LFEW was investigated in this study. RESULTS The fermentation efficiency of LFEW with lysozyme removed was significantly improved, and the sugar removal rate (2 g kg−1 Lactiplantibacillus plantarum, 37 °C, 7 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The surface hydrophobicity of EWP with/without the addition of antioxidants was investigated using ANS as a fluorescence probe, following the method described by Chen et al 20 . Samples were dissolved into deionized water to a protein concentration of 0.5 mg mL −1 ; 20 μL of ANS solution was added to 4 mL of the sample solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface hydrophobicity of EWP with/without the addition of antioxidants was investigated using ANS as a fluorescence probe, following the method described by Chen et al 20 . Samples were dissolved into deionized water to a protein concentration of 0.5 mg mL −1 ; 20 μL of ANS solution was added to 4 mL of the sample solution.…”
Section: Methodsmentioning
confidence: 99%
“…The surface hydrophobicity of EWP with/without the addition of antioxidants was investigated using ANS as a fluorescence probe, following the method described by Chen et al 20 Samples were dissolved into deionized water to a protein concentration of 0.5 mg mL −1 ; 20 μL of ANS solution was added to 4 mL of the sample solution. The mixture was incubated in the dark for 3 min, then an F-7000 fluorescence spectrometer (Hitachi, Tokyo, Japan) was used to scan the fluorescence spectra of samples from 400 nm to 600 nm at an excitation wavelength of 390 nm.…”
Section: Surface Hydrophobicitymentioning
confidence: 99%
“…However, the hardness of whole egg gels was decreased, along with a decrease in system pH. Similarly, Chen and Wang [ 28 ] found that Lactiplantibacillus plantarum fermentation (37 °C for 7 h) led to the decline of EW gel hardness, possibly due to the partial consumption of EW proteins, but promoted the formation of a bright gel appearance by consuming the residual glucose in EW. The above results indicated that lactic acid bacteria fermentation could improve gel qualities other than hardness.…”
Section: Strategies For Modifying the Gelling Properties Of Ew Proteinsmentioning
confidence: 99%